(untitled) (Research, Society and Development, 2023)
This research presents discusses the importance of hand hygiene against infectious and parasitic diseases, in order to Discover the possible consequences of not Using the “handwashing” method before, during and after care and what damage it can cause to doctors, students and patients in the hospital. Hospital environment. The objective is to identify whether the final year academics of the Assis Gurgaczs Foundation University Center perform and take due care in the face of opportunities that require care. The Applied methodol ogy was a quantitative descriptive study. Which consisted in the application of a questionnaire directed to the interns. In the face os the research, we Always obtained as a result more than 50% os the participants who carry out hygiene before the basic moments designated in the questions, and a small portion is not adherent, as well as Using water and soap for cleaning, and the materials for self-care of the hands are not Always availablre in healthcare settings. We conclude that sênior year studentes are more responsible for the prevention of infectious and parasitic diseases in most of the described moments and only a portion or a little less than half performs the action, using less frequently the hydroalcoholic solution.